Lamotrigine analysis in blood and brain by high-performance liquid chromatography - Castel-Branco, M. M. (2001)
A reversed-phase high-performance liquid chromatography assay was developed and validated to determine plasma and brain lamotrigine concentrations allowing pharmacokinetic-pharmacodynamic studies of this new antiepileptic drug in patients and laboratory animals. Lamotrigine and its internal standard were extracted, under alkaline conditions, from plasma and brain homogenate, into ethyl acetate; brain proteins were previously precipitated with trichloroacetic acid. The method was linear between 0.1 and 15.0 mg/l for plasma, with a detection limit of 0.008 mg/l, and between 0.1 and 5.0 mg/l for brain homogenate, with a detection limit of 0.023 mg/l. The method proved to be simple, useful and appropriate, not only for clinical and experimental research, but also for routine monitoring of lamotrigine concentrations in patients.